Socio-Demographic and Clinical Profile of Drug Resistant Tuberculosis Patients in a Tertiary Care Centre of Kolkata - Rivu Basu; Susmita Kundu; Debabani Biswas; Saswati Nath; Sarkar, Arnab; Archita Bhattacharya (Indian Journal of Community Health, 2021)
Background: Drug resistant tuberculosis is a major public health threat that hinders progress in tuberculosis control worldwide. In 2019, India contributed highest cases of TB (27%) Worldwide. In 2019, 3.3% of new TB cases and 18% of previously treated cases had MDR/RRTB worldwide and India (27%) had the largest share of the global burden. This study was done to find out the sociodemographic and clinical profile of drug resistant TB patients. Methodology: It is an observational descriptive study with cross-sectional design, conducted at the drug resistant tuberculosis centre of R. G. Kar Medical College of Kolkata, West Bengal. Study Population consisted of the patients who were registered for the DR-TB regimen. Study duration was July 2016 –March 2017. Pre-tested, semi-structured schedule was designed to capture their sociodemographic profile, treatment history, clinical findings and available medical records. Data were compiled in MS Excel and analyzed in IBM SPSS 23.0. Results: Out of 159 cases, 27% patients were between 21-30 years. Males were predominant (68.6%). Most patients (56.6%) were underweight (BMI<18.5kg/m2). HIV seropositivity was found in 4 (2.5%) cases. Among all cases, 81.1% had history of taking ATD and 34.4% was cured in previous episode of treatment. The commonest associated comorbidity was DM (15.7%). Rifampicin resistance (93.1%) was most common followed by Isoniazid (8.2%). Pallor was found among 94.3% patients. Most patients had bilateral (62.3%) and moderately extensive (57.2%) lesions in chest x-ray. Conclusion: DR-TB control should focus adequately on younger age group as numbers of resistance is increasing among them. Relapse in previously cured cases was found to be major contributor of DR-TB suspect cases. Though, Rifampicin resistance was so common but prevalence of resistance to 2nd line drugs is still low. Focus should be given on early detection of drug resistance in all TB cases and improvement of nutritional status of the TB patient.